2017
DOI: 10.1111/dme.13310
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Composite Autonomic Symptom Score 31 (COMPASS 31) for the assessment of symptoms of autonomic neuropathy in people with diabetes

Abstract: COMPASS 31 can represent a valid, easy-to-use, quantitative assessment tool for autonomic symptoms in diabetic neuropathy, with a fair diagnostic accuracy for both cardiovascular autonomic neuropathy and diabetic polyneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 18 publications
9
66
2
2
Order By: Relevance
“…In the present study, COMPASS 31 would appear to retain similar characteristics of diagnostic performance for CAN and DPN, with values of AUC up to 0.73, sensitivity up to 75% and specificity up to 65%, but with values for DPN being slightly lower than in the previous study. This may be due to differences between the populations of the present and previous study like a larger sample size (102 vs 73), a longer diabetes duration (18 vs 12 years), and a higher prevalence of DPN (52% vs 40%). However, an AUC of 0.73 for confirmed CAN supports overall fair diagnostic accuracy of COMPASS 31 (a value >0.7).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…In the present study, COMPASS 31 would appear to retain similar characteristics of diagnostic performance for CAN and DPN, with values of AUC up to 0.73, sensitivity up to 75% and specificity up to 65%, but with values for DPN being slightly lower than in the previous study. This may be due to differences between the populations of the present and previous study like a larger sample size (102 vs 73), a longer diabetes duration (18 vs 12 years), and a higher prevalence of DPN (52% vs 40%). However, an AUC of 0.73 for confirmed CAN supports overall fair diagnostic accuracy of COMPASS 31 (a value >0.7).…”
Section: Discussionmentioning
confidence: 55%
“…Recently, we validated COMPASS 31 for autonomic symptoms of diabetic autonomic neuropathy . In the validation study, in 73 participants with diabetes, we observed that COMPASS 31 scores were associated with CAN and DPN, related to their severity, and that COMPASS 31 TWS had a fair diagnostic accuracy for CAN and DPN with AUCs of 0.75 for CAN and 0.74 for DPN, and sensitivity and specificity of 75% and 65.5% for CAN and of 65.5% and 79.5% for DPN . Moreover, COMPASS 31 had good internal consistency with a Cronbach's coefficient of 0.73 …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations